Breaking barriers: the novel in vitro microdialysis system enables reproducing in vivo extraction efficiencies of linezolid - Müller, Felix Leon; Bindellini, Davide; Mikus, Gerd; Michelet, Robin; Kloft, Charlotte (European journal of pharmaceutical sciences, 2025)
Reported extraction efficiencies (EE) of the minimally invasive microdialysis (µD) technique for linezolid (LIN) varied in subcutaneous adipose tissue of obese 42.8 % (95 %CI:35.9 %-50.2 %) and non-obese patients 61.0 % (95 %CI:54.4 %-67.1 %). EE must be determined in vivo, as in vitro µD systems (EE=94.1 % for LIN) so far fail to reflect in vivo processes and conditions. This study aimed to develop an in vitro µD system capable of reproducing in vivo EE of LIN for different populations by mimicking tissue characteristics and processes limiting EE. Based on the static in vitro µD system two novel systems were developed: (i) mimicking catheter surrounding as artificially tissue structure (aTS) by creating a porous matrix using milling beads, and (ii) adding a surrounding flow as artificial tissue perfusion (aTP) through the aTS. While experiments using the aTS µD system resulted in a low EE of 33.2 % (95 %CI=31.8 %-34.7 %), adding aTP increased EE in a function of aTP, to a maximum of 97.2 % (95 %CI=91.1 %-104 %). The aTP µD system successfully reproduced the median reported in vivo EE range for LIN, matching EE for obese and non-obese at an aTP of 0.013 and 0.061 mL/min, respectively. By reproducing in vivo EEs for LIN, the novel aTP µD system (aTPMS) provides a platform for optimising µD settings in clinical trials, with future studies needed to explore its application to other substances.
Gesehen am 30.10.2025